The Correlation of Learning Strategies and Final Scores of Biomedical Blocks among Medical Students at Universitas Pattimura - Rubiyanti, Alfiyah; Bension, Johan Bruyif; Taihuttu, Yuniasih M.J.; Noya, Farah Ch.; Sanaky, Marliyati; Saija, Alessandra (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Medical students face a high learning load, especially in the biomedical block, which is the basis of medical science. Learning achievement on this block becomes important as it forms the basis for the next blocks. However, evaluations at the University of Pattimura Medical Faculty showed a decline in learning effectiveness in 2022/2023. Aims: This study aims to determine the correlation of learning strategies and final scores of biomedical blocks among medical students at Pattimura University. Methods: The research method used was descriptive-analytic with a quantitative approach and cross-sectional design. The study sample comprised 199 2023 biomedical block students from a population of 209 with a 95% response rate. Data was collected using the Motivated Strategies for Learning Questionnaire (MSLQ) and biology block 1 and 2 final grades. Data was analyzed using the Pearson correlation test at a significance threshold of α = 0.05. Results: All learning strategy components also showed significant positive correlations with biomedical block final scores (p<0.05; r=0.249 - 0.432).  Conclusion: It can be concluded that there is a positive correlation between learning strategies and the final scores of biomedical block, indicating that the better the learning strategy used by students, the higher the final scores obtained in biomedical block. Medical faculty may consider holding seminars on learning strategies for students.